A simple singing - Gould, Leslie, 1962- (The sisters of Lancaster county, 2018)
For years Marie Bachmann thought of herself as the "good" daughter. She was the most loving to their mother, the most dedicated to their Amish way of life. But when a Mennonite farmhand, Gordon Martin, shows interest in her she can't help but be flattered--until her mother sends her off to Florida. While there, Marie begins spending time with bad-boy Eli Jacob, the bishop's son from back home. When Gordon shows up in Florida to volunteer in a homeless shelter, her life becomes even more complicated. At the same time her aunt begins telling her of a Civil War-era ancestor and the woman's uncommon bravery . . . a story that begins to work at Marie's heart. Marie hopes returning home may simplify life, but Eli soon follows. As Marie grapples with whether she should court Eli or leave the church for Gordon, the story of Annie Bachmann shines a light on what God has for Marie's future.